2009
DOI: 10.1007/s00464-009-0379-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of laparoscopic surgical skills training outside the operating room: a long road

Abstract: No correlation was found between the three types of training outside the operating room, and no improved operative performance was observed. Possible explanations include too few subjects, training introduced too late in the learning curve, and training criteria that were too easy. Additionally, simulator training focuses on precision, which may actually increase task time. Awareness of these issues can improve the design of future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
0
64
1
1
Order By: Relevance
“…Two of the possible reasons proposed by the authors were small sample size and introduction of the didactic intervention too late in the learning curve [35]. These are applicable in our study as the number of participants who completed the study is limited and participants were not complete novices.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the possible reasons proposed by the authors were small sample size and introduction of the didactic intervention too late in the learning curve [35]. These are applicable in our study as the number of participants who completed the study is limited and participants were not complete novices.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Unfortunately, this is a rather frequent occurrence in educational studies [20,3,19,35,2]. Assessing the clinical impact of the study is methodologically challenging, as a number of participants did not have the opportunity to perform real laparoscopic cholecystectomies immediately after the completion of the study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Trained groups generally made fewer errors, and had less instances of supervising surgeon takeover than participants who did not have the training (17). Nine randomised trials of VR simulators and one of a video assisted simulator were identified to fill the inclusion criteria (Table 1) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In addition, two earlier studies from the ASERNIP-S review were included to the analysis (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…6,7,17,[25][26][27][28][29] The OSATS assessment tool assesses members on regard for tissue dissection, time and movement, instrument ergonomy, information of instruments, stream of operation, utilization of collaborator, and learning of methodology. GOALS rating scale 30 25 Also, in the same article, 100% of intervention members achieved the passing score level whereas it was just 37.5% of the control group. Researchers did not locate any statistical significance between the two groups; nonetheless, the members with low benchmark execution expanded their scores altogether after simulation training.…”
Section: Global Ratings (N = 7 Studies)mentioning
confidence: 99%